Modern pollen data from pristine taiga forest of Pechora-Ilych state nature biosphere reserve (Komi republic, Russia): first results - Lisitsyna, Olga; Smirnov, Nikolay; Aleynikov, Aleksey (Uniwersytet Mikołaja Kopernika w Toruniu, 2017)
The first results of modern pollen investigations from western slop of Ural Mountains presented. 33 modern pollen samples have been collected in June 2016 from four dominant forest types (Sphagnum, true moss, tall fern and tall herbs sections) in Pechora-Ilych state nature biosphere reserve (Komi republic, Russia). The detail record of surrounding vegetation was performed at every sampling point. Pollen assemblages are mostly dominated by tree pollen (Betula type, Pinus haploxylon type and Picea). The pollen assemblages and vegetation records will be statistically analyzed (clustering and correspondence analysis) to investigate how vegetation is reflected in pollen assemblages and for producing new series of PPEs.